2001
DOI: 10.1093/jxb/52.354.91
|View full text |Cite
|
Sign up to set email alerts
|

The hypocotyl chloroplast plays a role in phototropic bending of Arabidopsis seedlings: developmental and genetic evidence

Abstract: Chloroplasts of guard cells and coleoptiles have been implicated in the sensory transduction of blue light. The present study was aimed at establishing whether the chloroplast of the hypocotyl from Arabidopsis, another blue light-responding organ, has similar characteristics to that of sensory-transducing guard cell and coleoptile chloroplasts. Results showed that the phototropic curvature and arch length induced by blue light in Arabidopsis seedlings matched the distribution of mature chloroplasts in the bend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Not quite! In 2001, Jin and colleagues (Jin et al, 2001) found that hypocotyl phototropism in Arabidopsis appears to require mature chloroplasts and suggested the need for a functional xanthophyll cycle. Much of their conclusions are based upon a simple observation that mature chloroplasts are present within the bending region of the hypocotyl, and that RL pretreatments that increase BL-dependent phototropism also broaden the "zone of chloroplast maturation" within the hypocotyl.…”
Section: Chloroplastic Zeaxanthin As a Phototropic Sensor: Enigma Or mentioning
confidence: 99%
“…Not quite! In 2001, Jin and colleagues (Jin et al, 2001) found that hypocotyl phototropism in Arabidopsis appears to require mature chloroplasts and suggested the need for a functional xanthophyll cycle. Much of their conclusions are based upon a simple observation that mature chloroplasts are present within the bending region of the hypocotyl, and that RL pretreatments that increase BL-dependent phototropism also broaden the "zone of chloroplast maturation" within the hypocotyl.…”
Section: Chloroplastic Zeaxanthin As a Phototropic Sensor: Enigma Or mentioning
confidence: 99%
“…The pds2 mutant of Arabidopsis has a defective phytoene desaturase, is completely devoid of chlorophylls, and has an albino phenotype 30. In a blue light‐stimulated phototropic bending test, pds2 seedlings had no phototropic bending 31. Given that plants have more than one light sensory system and that we had only 2034 clones in our array, we cannot conclude that all light sensors are functional in these albino mutants.…”
Section: Discussionmentioning
confidence: 95%
“…Blue light (BL) is known to specifically affect several physiological processes, such as phototropism ( Jin et al 2001), stomatal aperture (Zeiger 2000), and chloroplast movement ( Jarillo et al 2001) in higher plants; uptake of monovalent anions in microalgae (Quiñones et al 1997); and synthesis of mycosporine‐like amino acids in macroalgae (Franklin et al 2001). One of the effects of BL that has been studied more in detail in macroalgae is the stimulation of red‐light (RL) saturated photosynthesis in brown algae.…”
mentioning
confidence: 99%